Stage-specific requirement for Isa1 and Isa2 proteins in the mitochondrion of Trypanosoma brucei and heterologous rescue by human and Blastocystis orthologues - Long, Shaojun; Changmai, Piya; Tsaousis, Anastasios D; Skalický, Tomáš; Verner, Zdeněk; Wen, Yan-Zi; Roger, Andrew J; Lukeš, Julius (Molecular microbiology, 2011)
IscA/Isa proteins function as alternative scaffolds for the assembly of Fe-S clusters and/or provide iron for their assembly in prokaryotes and eukaryotes. Isa are usually non-essential and in most organisms are confined to the mitochondrion. We have studied the function of TbIsa1 and TbIsa2 in Trypanosoma brucei, where the requirement for both of them to sustain cell growth depends on the life cycle stage. The TbIsa proteins are abundant in the procyclic form, which contains an active organelle. Both proteins are indispensable for growth, as they are required for the assembly of Fe-S clusters in mitochondrial aconitase, fumarase and succinate dehydrogenase. Reactive oxygen species but not iron accumulate in the procyclic mitochondrion upon ablation of the TbIsa proteins, but their depletion does not influence the assembly of Fe-S clusters in cytosolic proteins. In the bloodstream form, which has a downregulated mitochondrion, the TbIsa proteins are non-essential. The Isa2 orthologue of the anaerobic protist Blastocystis partially rescued the growth and enzymatic activities of TbIsa1/2 knock-down. Rescues of single knock-downs as well as heterologous rescues with human Isa orthologues partially recovered the activities of aconitase and fumarase. These results show that the Isa1 and Isa2 proteins of diverse eukaryotes have overlapping functions.
Keywords: mitochondrie; Protozoan Proteins; testy genetické komplementace; lidé; protozoální proteiny; Trypanosoma brucei brucei; Cell Survival; Mitochondrial Proteins; viabilita buněk; Gene Deletion; Blastocystis; Genetic Complementation Test; Mitochondria; mitochondriální proteiny; delece genu; Humans